Correlation Between Physical Activity During Covid-19 and the Level of Students' Physical Fitness - MOCHAMAD FERDIANSYAH; TITE JULIANTINE; ALIT RAHMAT (Universitas Pendidikan Indonesia, 2021)
Introduction: Physical activity is an activity that is usually maintained in standard conditions before the Covid-19 pandemic. Currently, students are mostly staying at home without doing physical activity. How is their physical fitness hold and increase their immunity? Is there a relationship between physical activity and fitness?. Purpose: This study aims to determine the relationship between physical activity during the covid-19 pandemic and students' level of physical fitness at SMA Negeri 1 Majalaya. Methods:The method used in this research is quantitative with a correlation research design. The population used in this study were students of class X SMA Negeri 1 Majalaya totaling 304 students with a sample of 30 students of class X IPA 1 taken using the purposive sampling technique. The research instruments used were the Physical Activity Questionnaire during COVID-19 and the Indonesian Physical Fitness Test (Tes Kebugaran Jasmani Indonesia/TKJI). This hypothesis test uses Pearson Product Moment correlation analysis to determine the positive correlation between physical activity during COVID-19 and physical fitness levels. Results:Of 30 students of SMAN 1 Majalaya (100%), there is one student (3.3%) in the very good category, one student (3.3%) in the good class, 13 students (43.3%) in the good category. Medium type. 13 students (43.3%) were poor, and two (6.7%) were in the inferior class. Conclusions: The results showed a relationship between physical activity during the COVID-19 pandemic and the level of physical fitness of students in class X IPA 1 SMAN 1 Majalaya in the 2020/2021 academic year, where a high level of physical fitness indicated good physical activity of students.